Ipsilateral hypoglossal nerve palsy following left hemithyroidectomy: Case report and review of literature. (2018) - Bu Bshait, Mohammed; Alyami, Hassan; Al-Osail, Emad; Al Arfaj, Haytham
Highlights: Hypoglossal nerve palsy is rare complication of oropharyngeal manipulation. Most of cases of neuro-paxic type which resolve spontaneously within 6 months. Corticosteroid use have not yet shown an advantage. Neck extension and strap muscles retraction during thyroidectomy may be considered predisposing factors. Abstract: Introduction: Hypoglossal nerve palsy (HNP) is a rare complication of airway management. Multiple factors have been postulated to contribute to its occurrence. Herein, we present a case of ipsilateral HNP following left hemithyroidectomy. Case presentation: A 47-year-old women presented complaining of left thyroid swelling for 1 year with no symptoms of compression or hormonal impairment. Ultrasound of the neck showed a 3 × 2 cm nodule in the left thyroid lobe without lymphadenopathy. Fine-needle aspiration revealed a follicular neoplasm. Left hemithyroidectomy was carried out uneventfully. Three hours postoperatively, the patient started to complaint of dysarthria, dysphagia and odynophagia with clinical sign of tongue deviation to the left side. Head and neck CT ruled out mass effect or ischemic event, and the diagnosis of left HNP was established. Four months postoperatively, the palsy was completely resolved. Histopathology examination of the thyroid nodule showed follicular adenoma, and no further intervention was provided. Discussion: Few cases of HNP are reported in the literature following oropharyngeal manipulation. Factors such as the type of surgery, position changes, and intubation characteristics have been linked to the incidence of HNP. Most of the cases recovered spontaneously, indicating a neuro-paxic type of injury. One case of HNP was reported following robotic total thyroidectomy, which was referred to as iatrogenic complication, and resulted in permanent paralysis. We believe that our case is the only reported case of transient ipsilateral HNP following a conventional left hemithyroidectomy. Conclusion: Strap muscles retraction and neck extension during thyroidectomy could predispose to HNP.